Concepções político-ideológicas e didáticopedagógicas dos participantes do IV ENESEB - Leandro Raizer; Daniel Gustavo Mocelin (Ciências Sociais Unisinos)
The article presents the results of a survey conducted with the participants of the 4th National Meeting on the Teaching of Sociology in Basic Education (ENESEB) held in 2015. The analysis includes the profile of the participants, pedagogical as well political and ideological conceptions, perceptions about the purpose of sociology in high school, and the difficulties and challenges for the qualification of the discipline. The results point to the existence of a heterogeneous profile, as well as significant differences in educational and political views among teachers of Basic Education and Higher Education, as well as students of Social Sciences. Major difficulties that were highlighted are the lack of teaching materials and their unsuitability for the teaching of the discipline as well as the lack of legitimacy vis-à-vis traditional disciplines; on the other hand, the low percentage of teachers with a university degree in Social Sciences and the need to qualify the teaching of the discipline appear as major challenges. Finally, despite the heterogeneous profile and different pedagogical and political views that were mapped, particularly the pragmatic and emancipatory ones, the survey reveals the existence of a consensus on the important role of the National Curriculum Guidelines (OCNS) for the qualification of the teaching of sociology as a discipline.